Genome sequencing and description of Oerskovia enterophila VJag, an agar- and cellulose-degrading bacterium - Vanessa Jag; Anja Poehlein; Frank R. Bengelsdorf; Rolf Daniel; Peter Dürre (Standards in Genomic Sciences, 2017)
Abstract A nonmotile, Gram-positive bacterium that shows an elongated and branching cell shape was isolated from soil samples from the botanical garden of Ulm University, Ulm, Germany. Here, the isolation procedure, identification, genome sequencing and metabolic features of the strain are described. Phylogenetic analysis allowed to identify the isolated strain as Oerskovia enterophila. The genus Oerskovia belongs to the family Cellulomonadaceae within the order Actinomycetales. The length of cells of O. enterophila ranges from 1 μm to 15 μm, depending on the growth phase. In the exponential growth phase, cells show an elongated and branching shape, whereas cells break up to round or coccoid elements in the stationary growth phase. The 4,535,074 bp long genome consists of 85 contigs with 3918 protein-coding genes and 57 RNA genes. The isolated strain was shown to degrade numerous complex carbon sources such as cellulose, chitin, and starch, which can be found ubiquitously in nature. Moreover, analysis of the genomic sequence revealed the genetic potential to degrade these compounds.